"It Is More Than Just about Music": Lifelong Learning, Social Interaction and Connection. Issue 1 (2nd January 2020) - Joseph, Dawn; Human, René
Abstract: For older people, participating in leisure activities enhances their sense of social, emotional, mental, spiritual and psychological wellbeing. This article reports on a case study that situated itself across two southern hemisphere countries – Australia and South Africa – and with two ensembles, namely: an instrumental ensemble in Melbourne (all musical readers); and a vocal ensemble in Clarens (all non-readers of music). The authors drew on Seligman's elements of positive emotion, engagement, relationships and meaning, and accomplishment (PERMA) to explore the ensemble members' engagement as "serious leisure and the wider community". Using qualitative case study methodology, they employed interpretative phenomenological analysis (IPA) as an organising tool to analyse and code their questionnaires and interview data. The findings are presented under three overarching themes, namely: meeting for serious leisure; music learning; and connecting with the wider community. While music engagement for older adults is an achievement in itself, sharing it with the wider community is considered most significant for the participants. Discussing two ensembles is a limitation in itself, therefore generalisations to other ensembles cannot be made. The article was written in 2020 during the COVID-19 lockdown period in both countries. Further research is planned across both countries to explore any implications the lockdown has had on the two groups once they are permitted to recommence rehearsals.